Dziedzictwo : historia prawdziwa - Roth, Philip (Lodz : Wydawnictwo Lodzkie, 1994)
Polish translation of Philip Roth's autobiographical work, "Patrimony."
Translation of: Patrimony.
Keywords: Roth, Philip -- Family; Roth family; Novelists, American -- 20th century -- Family relationships; Fathers and sons -- United States -- Biography